Charge breeding rare isotopes for high precision mass measurements: challenges and opportunities - Simon, Martin C.; Macdonald, T. D.; Bale, J. C.; Chowdhury, U.; Eberhardt, B.; Eibach, Martin Andreas; Gallant, A. T.; Jang, F.; Lennarz, A.; Luichtl, M.; Ma, T.; Robertson, D.; et al. (Physica scripta, 2013)
Ion charge breeding for Penning-trap mass spectrometry has been established as providing a precision increase that scales linearly with the charge state of the ion. Fast and efficient charge breeding is a precondition for the application of this approach to rare isotopes. However, in view of low yields and short half-lives the precision boost is partly compromised by unavoidable ion losses inherent to the charge breeding process. The mass spectrometer TRIUMFs ion trap for atomic and nuclear science is pioneering this field by coupling a Penning trap and an electron beam ion trap to the rare-isotope beam facility ISAC at TRIUMF. Here we present simulations that calculate and maximize the effective precision gain of time-of-flight ion-cyclotron-resonance measurements with highly charged ions of short-lived nuclides. In addition we compare the characteristics of measurements with singly and highly charged ions, and we summarize recent results that explored benefits of charge breeding that go beyond the precision increase.
Published 23 September 2013
Gesehen am 02.02.2022